Content marketing efforts in improving consumer purchase decision in Titip Weh - Muhammad Jembar Mubarrak; Ismail Yusuf; Mira Nurfitriya (Enrichment : Journal of Management, 2023)
The The purpose of this research is to find out: (1) How does marketing content describe and Titipin Weh consumers' purchasing decisions, (2) How does content marketing influence Titipan Weh's consumer purchasing decisions. This study uses 2 variables to test its influence, namely content marketing (X) purchasing decisions (Y). The objects in this study were 19 consumers from Titipin Weh. This study uses a quantitative research method with a descriptive and verification approach. From the results of the R test (Coefficient of Determination) the value of R Square (R²) obtained is 0.830, which means that the influence of marketing content on purchasing decisions is 83%, the remaining 17% is influenced by other factors not examined by the author.